Nature or Nurture- A Review of the Aetiology, Diagnosis, and Treatment of Attention Deficit Hyperactivity Disorder - Bull, Simon (Trinity Student Medical Journal, 2006)
Attention deficit hyperactivity disorder (ADHD) is a common neurobehavioural disorder characterised by developmentally inappropriate levels of hyperactivity, impulsiveness and inattention. Heritability data from twin studies of ADHD attribute about 75 percent of ADHD aetiology to genetic factors. The remaining 25 percent is attributed to environmental influences. ADHD affects 3 to 5% of children and a smaller percentage of adults. Diagnosis is based on criteria from the DSM-IV or ICD-10 and determined by a complete physical and behavioural evaluation. Psychoactive medication is consistently the most effective approach to managing ADHD and many effective pharmacological treatments are currently available.